Pengaruh slow deep breathing terhadap nyeri pada pasien post op apendisitis di rsud sleman - Ike Nurjana Tamrin; Elsye Maria Rosa; Dianita Subagyo (JHeS (Journal of Health Studies), 2019)
Slow Deep Breathing (SDB) is a breathing technique that can be used below 10 times per minute with a long phase of breathing. Objective: Effects of Slow Respiratory In the decrease of pain level in RSUD Sleman Method: Experimental design with pre-post test type without control group design. Samples of 30 respondents with Acidental Sampling Result: There is effect of Slow Deep Breathing on the pain decrease p 0,001@ 0,05 where P 0,05 can be concluded that there is significant difference. Conclusion: Slow Respiratory Exercise Slowly Reduces Pain Rate in Post-Appendicitis Patients at RSUD Sleman